Analysis of The Implementation of Public Relations Function at The Department of Industrial and Trading of Yogyakarta in Improving The Market Quality - Via Alfian Ika Agustina; Siti Fatonah; Muhammad Edy Susilo (Jurnal Ilmu Komunikasi, 2019)
Department of Industrial and Trading of Yogyakarta does not have any Public Relations Officer (PRO), but they continue its implementation of Public Relations function for increasing market quality. The objective of this study are to find out the implementation of Public Relations function from this department. Situational Theory of the Publics, The Concept of PR’s Function, and SWOT Analysis will be guide for this study. This study is a qualitative descriptive, in the interest of investigate, measuring, and interpreting the problems of this study. The results shows that this department is implement Public Relations functions in many kind of activities, include Press Agentry, Public Affair and Community Relations, Inovations, and Branding Strategy. Functions implemented by this department are: maintain a good relationship with their publics, create the corporate image, communications between organization and publics, and make programs for all the publics. Based on the results, SWOT Analysis, and Situational Theory of The Publics, the implementation has not been succeed. This is due to the inability of identifying the publics, fulfill its wishes, and find out the right strategy. In the other words, the failure comes out because there is no Public Relations in this department. The contribution of this research is in the form of policy recommendations to other organizations to implement the public relations function as much as possible to achieve the objectives of the program.